HARNESSING THE USE OF ARTIFICIAL INTELLIGENCE IN LANGUAGE ASSESSMENT: A SYSTEMATIC COMPREHENSIVE REVIEW - Al-Abbas, Hidayatul Ummah Al-Imamah; Halim, Halim Halim; Nurjati, Nunung Nurjati (Universitas PGRI Sumatera Barat, 2023)
This comprehensive review explores the utilization of Artificial Intelligence (AI) in language assessment and its transformative potential. Language assessment plays a vital role in education, employment, and societal integration. Language assessment has traditionally relied on human evaluators, who assess and score language performance based on standardized criteria. However, this manual assessment approach has limitations, including subjectivity, inter-rater variability, and scalability issues. With the rapid advancements in AI technologies, language assessment has experienced significant changes, offering more accurate, efficient, and innovative evaluation methods. The method used in this study is systematic review which critically examines the application of AI in language assessment, highlighting its benefits, challenges, and future prospects. The review covers various aspects, including automated scoring and evaluation, intelligent tutoring systems, natural language processing, advantages and benefits, challenges and considerations, and future directions. By harnessing the use of AI, language assessment can achieve unprecedented levels of objectivity, scalability, and personalization, while addressing ethical considerations. This review contributes to the understanding of AI's impact on language